Analisis Strategi Pemasaran Pada Penyedia Jasa Internet Speedy Di Kec. Taliabu Utara Kab. Pulau Taliabu Prov. Maluku Utara - Margaret, Merita; Kalangi, Johnny A. F.; Tamengkel, Lucky F. (JURNAL ADMINISTRASI BISNIS (JAB), 2019)
This study aims to analyze the marketing strategy of Speedy Internet Service Providers, especially the marketing mix applied. Then to find out the results of the analysis of Strengths, Weaknesses, Opportunities, and Challenges as well as an overview of the strategy so that it can be applied to increase product sales. By using SWOT, Matrix, EFAS, and IFAS research techniques and Cartecius diagrams. This research uses qualitative methods, namely case studies that produce descriptive data as outlined in words. Data collection techniques in this study the author made a direct visit to conduct personal interviews with Speedy Internet Service Providers and equipped with sales data several years back. The conclusions from the analysis carried out on the company's marketing strategy have carried out the marketing strategy correctly and precisely and in the calculation of the SWOT analysis as outlined in the Cartesius diagram the producers are in the position of quadrant 1, Growth. Which companies can develop, maintain and improve product quality so that people continue to believe in the products provided.